The Impact of Organizational Justice on Intention to Report Cases of Corruption in the Jordanian Public Sector - AL-shara, Maram Ibrahim; Al-Yakoub, Tamara Adel (The Arab Journal of Administration, 2025)
This study aims to identify the impact of organizational justice in its dimensions (distributive justice, procedural justice, and interactive justice) on the intention to report corruption cases in its dimensions (organizational support, employee protection, public service motive, and personal convictions) in the Jordanian public sector. To achieve the objectives of the study, the descriptive analytical approach was utilized by designing a questionnaire that was distributed to (720) employees, and (516) questionnaires valid for analysis were retrieved from (10) ministries and government institutions. The data were analyzed using the SPSS program to test the effect of the independent variable (organizational justice) on the dependent variable (intention to report corruption cases). The study revealed several results, the most important of which are: the existence of a statistically significant positive effect between organizational justice and the intention of Jordanian public sector employees to report cases of corruption. It has also been shown that the most influential dimension of organizational justice on the intention to report corruption cases is the interactive justice. It was also found that the most common dimension of the intention to report cases of corruption practiced in the Jordanian public sector is that of the “public service motive” .the study present several recommendations, including strengthening organizational justice in the Jordanian public sector, which directly impacts employees’ intention to report corruption cases, and the need to focus on procedural justice by allowing employees to participate in the decision-making process.